Overirradiance conditions and their impact on the spectral distribution at low- and mid-latitude sites - Zamalloa-Jara, M.A.; Sevillano-Bendezú, M.Á.; Ulbrich, C.; Nofuentes, G.; Grieseler, R.; Töfflinger, J.A. (Elsevier, 2023)
Lately, the photovoltaics community has shown an increased interest in overirradiance conditions as there is the possibility that such conditions might lead to malfunctions in photovoltaic systems. Varying irradiance levels, recurrence, and duration of such conditions have been reported worldwide, but experimental studies on the spectral distribution of overirradiance conditions are still scarce. This work analyses measured spectral irradiance of overirradiance conditions along with spectra under clear and cloudy sky conditions in three different sites at low- (Lima-Peru) and mid-latitudes (Madrid-Spain and Berlin-Germany) collected for two years. The Average Photon Energy (APE) was used as a representative index of the spectral distribution. For each site, taking the APE under clear sky into account as a reference, it could be shown that the spectra under cloudy skies are blue-shifted, and the overirradiance spectra are red-shifted independently of the location. The red-shift is proportional to the irradiance enhancement intensity. In addition, all sites have different degrees of blue–shift for cloudy skies, with Lima, Madrid, and Berlin exhibiting a difference in APE compared to clear sky conditions of 17 meV, 38 meV, and 43 meV on average, respectively. This difference in APE for the overirradiance conditions compared to clear sky conditions is also independent of the location with a mean value of (8 ± 1) meV. These spectral shift observations experimentally confirm prior assumptions that overirradiance conditions predominantly cause an enhancement of the direct spectral irradiance.
Keywords: Irradiance; Sky; Spectral power distribution; Environmental science; Spectral line; Solar irradiance; Atmospheric sciences; Latitude; Photovoltaics; Photovoltaic system; Meteorology; Physics; Optics; Astronomy; https://purl.org/pe-repo/ocde/ford#1.03.06